Heparin solution for maintaining peripheral venous catheter patency in children: a survey of current practice in italian pediatric units. (June 2014) - Bisogni, Sofia; Giusti, Francesca; Ciofi, Daniele; Festini, Filippo
<x xml:space="preserve">Abstract</x> Background: Prolonging the duration of peripheral venous catheters (PVC) as long as possible in children is a nursing priority. However, available studies provide conflicting evidence on what kind of flush/lock solution should be used to increase the life of PVCs in children. Objectives: To describe the clinical behavior of nurses working in Italian pediatric units with regards to PVCs flushing and locking practices. Methods: Cross-sectional study. Nurses were invited to participate using the network of the Italian Society of Pediatric Nursing Science. Those participating completed an online questionnaire available on a website established for this specific purpose. Results: 405 questionnaires were completed. Results: The majority of nurses reported using Normal saline solution (NS) to flush 22 gauge PVCs: 77.6% in children up to 6 months of age, 74.7% in children 6 months to 2 years, and 74.6% in children over 2 years. Nurses tend to use heparin solutions (HS) more frequently when a smaller gauge PVC is used (24 instead of 22) and when access is less frequent. The use of HS for PVC lock is more common in onco-hematology units (54.5% in children over 6 months with 24 gauge PVC), pediatric surgery units (35%), and in short-stay units (55.6%), whereas NS is used more frequently in Intensive care units (9.4%) and neonatology units (12.2%). Conclusion: Although the majority of respondents use NS, we found a high variability in practices among Italian nurses. More research on the effectiveness and safety of HS in maintaining the patency of PVCs is needed.